EMOTIONS AND REASONING IN MORAL DECISION MAKING - V. V. Nadurak (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the research is the study of relationship between emotional and rational factors in moral decisions making. Methodology. The work is primarily based on the analysis and synthesis of the main empirical studies of the problem, each of which uses the methods of those sciences in which they were conducted (neurosciences). Originality. In general, the process of moral decision making cannot be described by a single simple model that would see only emotional or rational factor in foundation of this process. Moral decision making is characterized by different types of interaction between emotions and rational considerations. The influence of emotional and rational factors on moral decision is nonlinear: moral decision, which person makes, isn’t proportional to those emotions that preceded it and isn't unambiguously determined by them, because rational reasoning and contextual factors can significantly change it. Similarly, the reasoning that precede the decision is not necessarily reflected in the decision, because it can be significantly corrected by those emotions that accompany it. Conclusions. The process of moral decision making involves complex, heterogeneous interaction between emotional and rational factors. There are three main types of such interaction: first, the reasoning serves to rationalize prior emotional response; second, there are cases when reasoning precedes emotional reactions and determines it; third, interaction between these factors is characterized by cyclic causality (emotion impacts reasoning, which in turn impacts emotions). The influence of emotions or rational reasoning on moral decision is nonlinear.